IMPLEMENTASI METODE AMSILATI DALAM KAJIAN KITAB KUNING DI PESANTREN SALAF - Chusnia Rahmawati; Muhammmad Rahman Arwani Jalaludin (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
This study presents the Amtsilati method as a provision in the study of the yellow book at the Al-Aqobah Al Hidayah Islamic Boarding School, Kwaron, Diwek, Jombang. The purpose of this research is to describe the Amtsilati learning methods as the provision of the study of the yellow book by the students. The approach in this study uses a qualitative approach, while the type of research used is descriptive with data collection methods using observation and interviews. The results of this study stated that the Amtsilati method as a provision in the study of the yellow book through two steps. The first step to do is connected with the new students who enrolling the Islamic boarding school and would be equipped with knowledge of tools to study the yellow book, namely the book of Amtsilati . Second, the students will apply the Amtsilati method in the study of the yellow book and conducted the reading methods both in the form of Sorogan and Bandongan.